2020
DOI: 10.1136/bmjopen-2019-036453
|View full text |Cite
|
Sign up to set email alerts
|

Built to last? The sustainability of healthcare system improvements, programmes and interventions: a systematic integrative review

Abstract: IntroductionThe sustainability of healthcare delivery systems is challenged by ageing populations, complex systems, increasing rates of chronic disease, increasing costs associated with new medical technologies and growing expectations by healthcare consumers. Healthcare programmes, innovations and interventions are increasingly implemented at the front lines of care to increase effectiveness and efficiency; however, little is known about how sustainability is conceptualised and measured in programme evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(115 citation statements)
references
References 66 publications
2
112
0
1
Order By: Relevance
“…This program evaluation uniquely focuses on sustainability of a clinical program targeting an outpatient physical rehabilitation setting. In two recent reviews on program sustainability, none occurred in similar departments (20,23). However, in one quasi-experimental study, behavior change strategies were implemented in a PT clinic with good uptake during the intervention, but poor sustainment at the three, six, or twelve-month follow up (24).…”
Section: Discussionmentioning
confidence: 99%
“…This program evaluation uniquely focuses on sustainability of a clinical program targeting an outpatient physical rehabilitation setting. In two recent reviews on program sustainability, none occurred in similar departments (20,23). However, in one quasi-experimental study, behavior change strategies were implemented in a PT clinic with good uptake during the intervention, but poor sustainment at the three, six, or twelve-month follow up (24).…”
Section: Discussionmentioning
confidence: 99%
“…One contributing factor to this difficulty is the inconsistent use of definitions [ 3 – 7 ]. In a systematic review of 92 studies about how sustainability is conceptualized and measured in evaluations of healthcare improvement programs and interventions, 53 studies explicitly mentioned sustainability, yet only 27 studies provided a definition, and 32 definitions were used [ 8 ]. For our study, we used the Moore et al (2017) [ 6 ] definition of sustainability: “(1) after a defined period of time, (2) the program, clinical intervention, and/or implementation strategies continue to be delivered and/or (3) individual behavior change (i.e., clinician, patient) is maintained; (4) the program and individual behavior change may evolve or adapt while (5) continuing to produce benefits for individuals/ systems” [ 6 ] (p.6); and the Shaw et al (2018) [ 9 ] definitions of spread and scale with a main difference being that spread is for “complex” problems where following a specific formula may not work and extensive adaptation may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…The need for effective QI programs to be sustained, spread, and/or scaled-up is self-evident; however, there is minimal research in this area [ 2 4 , 8 , 14 16 ]. As diabetes is a chronic disease with high impact in terms of health care resource utilization, costs, societal impact, and health outcomes [ 17 19 ], more consideration for how to continue effective diabetes QI programs is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies within implementation science often focus on initial program or intervention adoption and implementation, placing less emphasis on sustainability [8]. In two recent reviews of sustainability, the authors found relatively few studies focusing on sustainability, most of which were of limited quality and methodological rigor [9,4,10]. Research on sustainability is limited in part because data collection for grant funded studies is typically not carried out past the funding end date and is beyond the scope of many public health and health services studies [11].…”
mentioning
confidence: 99%
“…Research on sustainability is limited in part because data collection for grant funded studies is typically not carried out past the funding end date and is beyond the scope of many public health and health services studies [11]. Consequently, there have been recent calls for increased attention to sustainability research, theory, and methods [4,10].…”
mentioning
confidence: 99%